2021
DOI: 10.1016/j.jped.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary manifestations of COVID-19 in children: a comprehensive review and pathophysiological considerations

Abstract: Objective The aim of this review was to summarize the most common extrapulmonary manifestations in pediatric patients with COVID-19, as well as to discuss clinical, epidemiological, and pathophysiological aspects of these clinical presentations in children. Source of data An extensive search of literature was performed in order to identify pediatric cases with extrapulmonary manifestations between January 1, 2020 and June 21, 2020. Generic keywords, such as “Novel coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
12

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 83 publications
(179 reference statements)
1
42
0
12
Order By: Relevance
“…Finally, 45 systematic reviews met the inclusion criteria and were included in this overview. 11 55 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 45 systematic reviews met the inclusion criteria and were included in this overview. 11 55 …”
Section: Resultsmentioning
confidence: 99%
“…Cutaneous lesions of COVID-19 occur in more than 8% of hospitalized children 115 and are the 7 th most common extrapulmonary manifestation. 116 There are several case reports and case series of various cutaneous eruptions in COVID positive children. Children with COVID-19 and skin manifestations carry an overall better prognosis than those without.…”
Section: Pediatric Covid-19mentioning
confidence: 99%
“…Severe acute respiratory syndrome causing coronavirus (SARS‐CoV‐2) is a new coronavirus responsible for the pandemic named coronavirus disease 2019(COVID‐19). Although the pathogenesis of the disease has not been completely understood yet, it may cause clinical pictures with various degrees of multisystem involvement 1,2 …”
Section: Characteristics Of Patients % (N)mentioning
confidence: 99%
“…Studies have indicated that coronavirus can also cause cutaneous lesions; however, specific cutaneous symptoms of COVID‐19 infection have not been disclosed yet. The prevalence of cutaneous manifestations in COVID‐19 patients was between 0.2% and 20.4% in the recently published studies 1,3‐6 and 3.4% in a review including 28 studies where the patients aged between 0 and 18 years age had COVID‐19 2 . In this respect, we aimed to analyze the incidence and the types of cutaneous manifestations associated with COVID‐19 infections in pediatric patients.…”
Section: Characteristics Of Patients % (N)mentioning
confidence: 99%